Hubungan Kadar Neuron Specific Enolase Serum dengan Subtipe dan Tingkat Keparahan pada Pasien Stroke Iskemik Akut - Dhani Arief Prandana; Syarif Indra; Dedi Sutia; Restu Susanti; Fanny Adhy Putri; Gunawan Septa Dinata (Jurnal Ners, 2025)
Background: Acute ischemic stroke is a serious medical condition with potentially life-threatening consequences. It occurs when cerebral blood flow is obstructed by vascular occlusion, resulting in brain tissue injury. Neuron Specific Enolase (NSE) is a biomarker used to assess the extent of neuronal damage in patients with ischemic stroke. This study aims to evaluate the association between serum NSE levels, stroke subtypes, and stroke severity in patients with acute ischemic stroke. Methods: This observational study employed a cross-sectional design and included 67 patients with acute ischemic stroke. Serum NSE levels were measured using the ELISA method. Stroke subtypes were determined according to the TOAST classification, and stroke severity was assessed using the NIHSS score. Statistical analysis was performed to evaluate the association between serum NSE levels, stroke subtypes, and severity. Results: The mean serum NSE level was 14.038 ng/ml. Large artery atherosclerosis (LAA) was the most prevalent subtype with a moderate severity level. Statistical analysis showed a significant association between serum NSE levels and stroke subtype (p = 0.021) and severity (p = 0.034) in patients with acute ischemic stroke. Conclusion: Serum NSE levels are significantly associated with both stroke subtype and severity in patients with acute ischemic stroke.